The potential of secondary metabolites of Trichoderma viride T1sk extracted with organic solvents etil acetate and butanol in suppressing the growth of Colletotrichum gloeosporioides in vitro - Nurbailis, Nurbailis; Yanti, Yulmira; Jamaan, Akmal; Rahayu, Silva Dika (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
The control of Colletotrichum gloeosporioides, the causal agent of anthracnose in chili, is typically achieved through synthetic fungicides, which pose risks to both the environment and consumers. As a safer alternative, microbial-derived biopesticides offer an environmentally friendly solution. This study aimed to evaluate the potential of secondary metabolites produced by Trichoderma viride T1sk, extracted using organic solvents with different polarities (ethyl acetate and butanol), to inhibit the growth of C. gloeosporioides in vitro. A Completely Randomized Design (CRD) was used, comprising three treatments with six replications, each consisting of two petri dish units. The treatments included: (A) ethyl acetate extract, (B) butanol extract, and (C) a control. The media poisoning method was employed to assess the antifungal activity of the extracts. Key parameters observed were colony area, conidial count, conidial germination rate, and propagule density of C. gloeosporioides. The results demonstrated that both ethyl acetate and butanol effectively extracted antifungal secondary metabolites from T. viride T1sk. In general, these metabolites significantly suppressed the growth of C. gloeosporioides. Among the solvents tested, butanol exhibited the highest efficacy in extracting antifungal compounds and consistently achieving the strongest inhibition across all observed variables.